Representation of People with HIV/AIDS in The Jakarta Post and Jakarta Globe: A Critical Discourse Analysis - Gigit Eklesia; Akhyar Rido (Universitas Teknokrat Indonesia, 2020)
This study aims to understand representational meanings from the transitivity choices used by news reports from The Jakarta Post and Jakarta Globe in reporting people with HIV-positive cases and exposing the underlying ideology behind the representation. Fairclough’s three-dimensional concept in Critical Discourse Analysis (CDA) was applied in this study. The study also relied on Halliday’s systemic functional grammar, particularly in the transitivity analysis. Two selected articles were collected from The Jakarta Post and Jakarta Globe newspapers. The findings revealed that both news media dominantly report people with HIV/AIDS through material process, then followed by verbal process and relational process. Next, the study found that people with HIV/AIDS are represented as discriminated and threatened group in The Jakarta Post; meanwhile, they are represented as a mistreated group in Jakarta Globe. Last, the study found that The Jakarta Post attempts to construct that people with HIV/AIDS need to be more accepted and protected; meanwhile, Jakarta Globe attempts to construct an idea that people with HIV/AIDS need to be given more attention. To sum up, the combination of the both theories is substantially advantageous in the discourse to expose ideology.